Elementary school counselors’ perceptions of the utility of play therapy - Carleton, Nicole M. (Kansas State University, 2022)
Play is fundamental to the optimal growth and development of children. Utilizing play therapy with children who require mental health support and intervention is of significant benefit to the child, as it allows them to express their needs through play, their first language. School counselors who work with elementary-aged students may find play therapy to be a beneficial component of their comprehensive school counseling program. However, little is known about the use of play therapy by elementary school counselors, the training they have received in play therapy, or whether they perceive it as a useful intervention with their elementary-aged students. This study utilized a one-group pretest-posttest design to learn about elementary school counselors’ perceptions of play therapy utility and if providing information about play therapy changed these perceptions. Participants were a sample of practicing elementary school counselors in the United States (n = 191) who answered questions about the utility of play therapy both before and after receiving information about play therapy. Overall, participants found play therapy to be useful even before receiving information about it. Results indicated a statistically significant increase in the rating of play therapy utility after viewing a brief educational video about play therapy. These initial perceptions and the increase in perceptions did not vary significantly based on the community classification or low-income status of where an elementary school counselor worked, but statistical significances were detected based on the status of their reported training in play therapy. Implications of the findings and recommendations for future research and practice on this topic, including barriers to training in and use of play therapy by school counselors, are further discussed.
Keywords: Play therapy; Perception; Counselors; School counselors